Performance Based Islamic Performance Index (Study on the Bank Muamalat Indonesia and Bank Syariah Mandiri) - Siti Aisjah; Agustian Eko Hadianto (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
The development of Islamic base banks in Indonesia in recent years show rapid growth. The main challenge for Islamic base banks is how to raise belief from the stakeholders. Stakeholder expectations of the Islamic banks is different from a conventional bank. Since, Islamic banks are built on basic principles of Islamic economics. Therefore, we need a tool to evaluate and measure the performance of Islamic base banks. Islamicity Performance Index is a method which can evaluate the performance of Islamic base banks not only their financial but also justice principles, halal (lawfulness), and tazkiyah (sanctification). There are six financial ratios which are measured from Islamicity Performance Index:profit sharing ratio, zakat performance ratio, equitable distribution ratio, directors-employees welfare ratio, Islamic investment versus non-Islamic investment ratio, Islamic income versus non-Islamic income. This research is intended to figure out the performance of Islamic base Bank in Indonesia based on Islamicity Performance Index. The samples are the Bank Muamalat Indonesia and Bank Syariah Mandiri. Sources of data are the financial reports of Bank Muamalat Indonesia and Bank Syariah Mandiri in 2009–2010 period.The results show that the financial performance of Islamic Base Bank in Indonesia during 2009-2010 period have ”quite satisfactory level of valuation. However, there are two unsatisfactory ratios. They are zakat performance ratio and director-employee welfare contrast ratio. It shows that zakat issued by the Islamic base bank in Indonesia is still low and the contrast of the director-employee welfare is still huge.